Stability Analysis and Optimal Design for Virtual Impedance of 48 V Server Power System for Data Center Applications - Chien-Chun Huang; Sheng-Li Yao; Huang-Jen Chiu (Energies, 2020)
In the past literature on virtual impedance to series systems, most of the discussion focused on stability without in-depth research on the system design of the series converter and the overall output impedance. Accordingly, this study takes an open-loop resonant LLC converter series-connected closed-loop Buck converter as an example. First, the conditions required for the direct connection of the small-signal model in the series, the effect of feedback compensation on the input impedance of the load stage, the operating frequency, and passive components of the two-stage converter are discussed in detail―the relationship between the matching and the output impedance. Afterwards, a mathematical model is used to discuss the effect of adding parallel virtual impedance on the output impedance of the overall series converter and then derive an optimized virtual impedance design. Finally, an experimental platform of 48 V to 12 V and maximum wattage of 96 W are implemented. The output impedance of the series converter is measured with an impedance analyzer to verify the theoretical analysis proposed in this paper.